Estimation of Vitamin C and the Fructose Levels in Some Medicinal Plants and their Effects on Iron Bioavailability in Rats - Al-rubaye, Zainab Samir; Al-Shahwany, Ayad W. (Iraqi Journal of Science, 2022)
Iron deficiency is considered as a common problem facing the general world population. In the current research, experiments were conducted to evaluate the effects of aqueous extracts of Acacia senegal (Gum Arabic, GA), Spinacia oleracea (spinach), Zea mays (corn), and Capsicum annuum (red chili pepper) on iron and ferritin levels in rats. Vitamin C and fructose levels were first estimated in these plants by using High-Performance Liquid Chromatography (HPLC). The results showed that the GA extract contained the highest level of fructose (853 mg.L-1), followed by red chili pepper (635 mg.L-1), corn (521 mg.L-1), and spinach (271 mg.L-1) extracts. Also, the results of vitamin C estimation showed levels of 3.376, 0.645, 0.579, and 0.347 mg/ml in the extracts of spinach, red chili pepper, corn, and GA, respectively. Next, thirty male albino rats (age 8-12 weeks, weight 120-200 g) were divided randomly into six groups, each kept in a separate polypropylene rat cage. Treatments of rats with various plant extracts were conducted following a CRD complete random design, with five replicates for each treatment. The results of lipid profile test revealed that GA treatment caused the highest reduction in the serum levels of TC, TG, LDL, VLDL, and HDL in the treated rats (76.25, 55.25,23, 15.25, and 38 mg/dl , respectively), as compared to the other plant extracts. Evidence from this study suggests that the higher serum level of fructose in the group of rats treated with all plant extracts enhances the process of ferritin formation, possibly via increasing the level of bioavailable iron.